Developing and Establishing Biomechanical Variables as Risk Biomarkers for Preventable Gait-Related Falls and Assessment of Intervention Effectiveness - Grabiner, Mark D.; Kaufman, K.R. (Frontiers in Sports and Active Living, 2021)
The purpose of this review is to position the emerging clinical promise of validating and implementing biomechanical biomarkers of falls in fall prevention interventions. The review is framed in the desirability of blunting the effects of the rapidly growing population of older adults with regard to the number of falls, their related injuries and health care costs. We propose that biomechanical risk biomarkers may be derived from systematic study of the responses to treadmill-delivered perturbations to both identify individuals with a risk of specific types of falls, such as trips and slips as well as quantifying the effectiveness of interventions designed to reduce that risk. The review follows the evidence derived using a specific public health approach and the published biomedical literature that supports trunk kinematics as a biomarker as having met many of the criteria for a biomarker for trip-specific falls. Whereas the efficacy of perturbation training to reduce slip-related falls by older adults appears to have been confirmed, its effectiveness presently remains an open and important question. There is a dearth of data related to the efficacy and effectiveness of perturbation training to reduce falls to the side falls by older adults. At present, efforts to characterize the extent to which perturbation training can reduce falls and translate the approaches to the clinic represents an important research opportunity.